From Plasmacytoma to Rib Tuberculosis: The Case of A Breast Mass With An Unexpected Diagnosis - Hafedh Abbassi; Badra Bannour; Sarra Yacoub; Ekram Guerbej; Imen Bannour; Samir Hidar; Moncef Mokni (European Journal of Breast Health)
Tuberculosis (TB) of the rib is an uncommon manifestation of extrapulmonary TB that can pose significant diagnostic challenges, especially when presenting as a breast mass. We report the case of a 74-year-old woman who presented with a left breast lump, initially suspected to be a plasmacytoma due to its imaging characteristics and clinical history. The mass was surgically excised, and histopathological analysis revealed granulomatous inflammation with caseous necrosis, suggesting TB. TB-polymerase chain reaction confirmed the diagnosis, despite negative Ziehl-Neelsen staining. The patient was treated with anti-tubercular therapy for twelve months, resulting in a favorable clinical outcome. This case highlights the importance of considering rib TB in the differential diagnosis of breast masses, particularly in endemic areas, and underscores the role of comprehensive diagnostic evaluations for timely and effective treatment.